Pembiayaan Perumahan Syariah Berbasis Akad Murabahah bil Wakalah dalam Perspektif Fatwa DSN No.04/DSN-MUI/IV/2000 - Tasyana Rahmadini; Ali Trigiyatno; 'Alamul Yaqin (Fakultas Syariah Universitas Islam Negeri (UIN) K.H. Abdurrahman Wahid Pekalongan, 2022)
This article discusses the process of contract and mortgage financing based on a murabahah bil wakalah contract at PT Bank BTN Syariah Pekalongan branch office from the perspective of DSN Fatwa No.04/DSN-MUI/IV/2000. This type of research is a field research (field-research) with a qualitative approach. Sources of data in the form of primary and secondary data, primary data obtained by interview and observation techniques while secondary data obtained by documentation. The subject of this research is PT. Bank BTN Syariah Pekalongan Branch Office and Customers, while the object is the settlement in accordance with DSN Fatwa No.04/DSN-MUI/IV/2000 in the Murabahah bil Wakalah contract. And data analysis using descriptive qualitative. The practice of the Murabahah Bil Wakalah contract At PT Bank BTN Syariah Pekalongan Branch Office, most of the practices of the Murabahah bil Wakalah contract have complied with the provisions of the DSN Fatwa No. 04/DSN-MUI/IV/2000. However, there are still provisions that have not been fulfilled, namely the financing of the murabahah contract directly before the end of the wakalah contract or the house being traded in principle does not belong to the bank so that it is not in accordance with the provisions of the DSN Fatwa No.04/DSN-MUI/IV/2000 which states that the bank wants to represent the customer for the purchase of an item from a third party, the murabahah sale and purchase contract must be executed after the goods have become the property of the bank.